Assessment of Clinical Efficiency of Manual K- files, Kedo-S Plus and Fanta AFTM Pediatric Rotary Files During Pulp Therapy of Primary Teeth: A Clinical Trial (Academia Journal of Medicine, 2024)
The objective is to evaluate the instrumentation time required  for primary molar root canal preparation using two pediatric  rotary file systems (Kedo-S Plus & Fanta AFTM Baby) in  comparison to manual K-files.  60 lower primary molars of healthy youngsters, ages 4-8 years  were participated. Three groups (n=20) received a random  assignment of molars. Kedo-S Plus and Fanta AFTM Baby rotary  systems were used to prepare groups I and II, while a manual K file was used to organise group III, stopwatch was used to  estimate the instrumentation time. The result shows that the first group had the lowest instrumentation time (78.8 seconds),  followed by group II and the manual-K file group (p
Keywords: Pulpectomy; Deciduous tooth; Rotary files